PENGARUH KRIM EKSTRAK JINTAN HITAM (Nigella sativa) TERHADAP KADAR KOLAGEN DAN HIDRASI KULIT PADA TIKUS (Rattus norvegicus) GALUR WISTAR JANTAN YANG DIPAPAR SINAR ULTRAVIOLET-B - Winda Sari; Linda Chiuman; Sahna Ferdinand Ginting; Chrismis Novalinda Ginting (BERITA BIOLOGI, 2020)
Photoaging is caused by exposure to sunlight and ultraviolet radiation (UV-B) through the reactive oxygen species (ROS) molecules formation, resulting in decreased levels of collagen. It is characterized by wrinkles, sagging and rough surfaces. Black cumin has been used in medicine due to its high antioxidant potential. The aim of this study is to identify the effect of black cumin cream on collagen levels and hydration of the skin of Rattus norvegicus exposed to ultraviolet-B rays. This is experimental study in which 30 male Wistar strain rats were classified into 6 sub-groups, namely the KN group (without treatment), KP (getting Nivea cream moisturizer), P1 (basic cream ), P2 (black cumin seed extract cream 0.25%), P3 (cream 0.5%) and P4 (cream 0.75%). P4 rat collagen levels increased significantly before and after the intervention (24 ± 2.23 vs 42.6 ± 14.6, p <0.05).Cream with lower concentrations did not provide a significant increase (p> 0.05). P4 rats also showed increased skin hydration (38.6 ± 19.3 to 63.0 ± 4.47 (p <0.05)), and this was not found in other groups. The administration of topical black cumin seed extract 0.75% can inhibit decreased levels of collagen and increase skin tissue hydration.